Service domestique, sexualité, race et héritages coloniaux à l’Île Maurice - Colette Le Petitcorps (Glad!)
Instead of focusing on sexual relations in domestic service work, this article is about sexuality as an object of discourse on domestic service relations in Mauritian contemporary society. Is questioned the way the fact of speaking on the sexual aspect of domestic service relations does order and legitimate the current social hierarchies, by turning back to the racial categories of colonial inheritance. With an exploratory approach, the analysis confronts the discourses of some “maids” and “Madams” which bring together the social imaginaries of race and sexuality around the topic of maid’s work. The empirical data analysis helps to grapple with the complexity of colonial heritage that emerges from the reintroduction of racial categories exactly where the social relations are refurbished.